Evaluation of Active Protection Systems for Fire Extinguisher at Locomotive Depot - Putri, Kholfana Bintan Maula Aditya; Limanda, Evelyne Martha; Fahmi, Muhammad Alif Indra; Syamila, Ana Islamiyah; Prana, Yoka Bismayuda (Journal of Public Health for Tropical and Coastal Region, 2024)
Abstract Introduction: A fire is an accident that can occur in the railroad industry. Locomotive depots have various work processes and fuels that can cause medium-II fires. An active protection system using fire extinguishers is one of the preventive efforts that can be performed along with evaluation. However, fire extinguisher evaluations based on the regulatory standard have never been performed in the Locomotive Depot of Daop 9. This study aimed to evaluate the suitability of a Fire Extinguisher at PT KAI Daop 9 Jember Locomotive Depot with Permenakertrans No. 4 of 1980.Methods: This study was an evaluation research. Data collection was conducted through semi-structured interviews to the Locomotive Depot Facility Supervisor, observations using a checklist sheet, and measurements. Data were analyzed using the univariate method and are presented using tables and narratives.Results: The Locomotive Depot had several hazards from welding, locomotive electrical systems, fuel, and cigarette butts. A fire prevention program consists of providing a fire protection system, training, reporting, and forming an emergency response team. The locomotive depot had 13 powder fire extinguishers weighing 3.5-12 kg. The suitability of fire extinguisher installation and maintenance is sufficient category with 66.7% for installation and 74.3% for maintenance.Conclusion: The Daop 9 Jember Locomotive Depot has several fire hazard risks and prevention programs. The suitability of the installation and maintenance of fire extinguishers was in a sufficient category. It is necessary to optimize fire prevention programmes through the cooperation of various parties to enforce applicable regulations.